Voltammetric determination of Chromium(VI) using a gold film modified carbon composite electrode - Kachoosangi, RT; Compton, R (2013)
Chromium(VI) should be monitored and controlled in the environment, since it is introduced into the environment from several sources and it is both toxic and carcinogenic being harmful to the health of human and also animals. A simple voltammetric technique for quantification of the chromium(VI) is presented in this paper. The technique is based on the direct linear sweep voltammetric reduction of Cr(VI) on a gold plated carbon based composite electrode, without any accumulation stage, or any complexing agent. The effect of supporting electrolyte matrix, pH and also scan rate is investigated. The effect chloride ions interference is also investigated. The calibration curve for chromium(VI) detection using the proposed method shows linearity from 20 μg/L to 2000 μg/L with a detection limit of 4.4 μg/L achieved without any accumulation or pre-concentration process. The method was also successfully used for determination of Cr(V) in river sample water, where recovery of 96% was achieved. © 2013 Elsevier B.V.